FOOD SAFETY AND QUALITY POLICY IN THE REPUBLIC OF SERBIA - Popović, Vesna; Vuković, Predrag; Ćosić, Milivoje (Economics of Agriculture, 2017)
Food safety and quality have a decisive impact on the placement of agro-food products on the domestic and world market. In the sector of agriculture and food industry in Serbia a range of public and private standards, mandatory and voluntary is applied, covering the different stages of the supply chain and different levels of communication (with business partners or consumers). However, still a small number of primary agricultural producers are certifed to Global G.A.P., organic production and products with a geographical indication. A better situation is in food processing industry and export. Many of food processors, especially suppliers of global retail chains are, in addition to HACCP, certified to ISO (9001, 22000) and exporters to BRC and IFS standards. The loss of the market due to failure to respect the safety standards and product quality is a real danger, which mustbe averted by an active state support policy.